Quantitative phosphoproteome analysis of cisplatin‐induced apoptosis in Jurkat T cells. Issue 11 (8th June 2017) - Tran, The Trung; Strozynski, Margarita; Thiede, Bernd
Abstract : Protein phosphorylation is one of the most important post‐translational modifications (PTMs) due to its vital role in cellular functions and signaling pathways. Protein phosphorylation is also known to be involved in the regulation of apoptosis. Previously, we have performed a SILAC‐based analysis of tyrosine phosphorylated peptides of cisplatin‐induced apoptotic Jurkat T cells. Here, we analyzed the global phosphorylation profile by enrichment of serine/threonine/tyrosine phosphorylated peptides using TiO2 beads. More than 7000 phosphopeptides of more than 2500 phosphoproteins were identified in four biological replicates. Using two different normalized collision energy (NCE) values for fragmentation by higher‐energy collisional dissociation (HCD) revealed complementary results. HCD with NCE 25 accounted for 31% and NCE 35 for 12% uniquely identified phosphopeptides, whereas 57% were found at both NCEs. Different peptide lengths and amino acid compositions were observed at different NCE. A phosphopeptide database was generated out of the results obtained using the Swiss‐Prot protein database in order to find differences in regulation of specific phosphorylated sites within multiphosphorylated proteins. Several members of the MAPK signaling pathway were found to be upregulated in apoptotic compared to control cells. Changes of phosphorylation of the transcription factors JUN and ATF2 during apoptosis was confirmed by Western blotting.